Population Estimation Using Geographic Information System and Remote Sensing for Unorganized Areas - Kamel Allaw; Jocelyne Adjizian Gerard; Makram Zouheir Chehayeb; Nada Badaro Saliba; Abbas Rammal; Zainab Jaber (Geoplanning: Journal of Geomatics and Planning, 2020)
Population estimation using remotely sensed data has been largely discussed in the literature relative to human geography. However, the previously established models can be applied on organized areas (mainly urban areas) but they are not suitable for unorganized areas which already suffer from a lack of population data. So, the aim of this study is the establish a statistical model for population estimation based on remote sensing data and suitable for unorganized areas. To do so, the morphological characteristics have been studied and a bivariate analysis was carried out to determine factors having a strong relationship with population data as a first step. Second, factors with strongest correlations have been chosen to establish the required model. As a result, an equation has been generated which relates the population data to building volume, density of roads, number of nodes, actual urban areas, and urban trend.